Analisis Pengaruh Digital Divide Terhadap User Satisfaction dan Individual Performance pada Pengguna Sistem Informasi Akademik - Niken Ayu Setifani; Dwi Rolliawati; Noor Wahyudi (Universitas Diponegoro, 2022)
Since the pandemic, various sectors have shifted their online activities, which have also been applied to education, specifically in universities. Universities have individuals with different conditions, which encourages the management to provide information systems that support the implementation of activities at these universities. Not only learning activities but also academic administration is generally known as the Academic Information System (AIS). AIS was implemented at the Health Polytechnic Ministry of Health in Surabaya, labelled Academic Management Information System (SIM Akademik). This polytechnic has campuses spread across several cities in East Java. Each campus has different resources, thus supporting the digital divide. This study’s objective was to determine the effect of the digital divide, user satisfaction, and individual performance of Academic SIM users. These examine could develop the theory of the three variables and determine the digital range between campuses and user satisfaction. According to the results of three hypotheses tested using PLS-SEM with the Disjoint Two-Step Approach method, the digital divide had a significant positive effect on user satisfaction, the same as user satisfaction on individual performance. The digital divide had a positive, however not statistically significant, impact on individual performance. Furthermore, there was a digital divide between campuses in two aspects of measurement, and academic SIM user satisfaction is greater than 85% in all aspects of size. Employees experience the most significant performance improvement when using Academic SIMs, followed by students at 85,76 % and lecturers at 79,44 %.